INTERDISCIPLINARY MODULAR EDUCATIONAL TECHNOLOGY OF THE DEVELOPMENT OF AESTHETIC COMPETENCE IN THE TEACHING OF BOTANY IN FUTURE BIOLOGY TEACHERS - Ismailov Khurshid Esirgapovich (Лучшие интеллектуальные исследования, 2024)
Abstract: This article provides information about the effective use of the modular education system and its importance and structure.